Pytania wokół roli tożsamości w wychowaniu - Olbrycht, Katarzyna (Horyzonty Wychowania, 2017)
The text is an attempt to consider the questions connected with the role of identity in education. The author suggests a few questions – problems, presenting them in the light of the selected theoretical standpoints. Finally, she justifies the need for recognizing identity in both theory and practice of education, emphasising the inevitability of an extended pedagogical reflection in this field, as well as making specific anthropological-philosophical assumptions. She also formulates several tasks connected with the educational activity aiming for the formation of identity. In conclusion, the author pays attention to the need for the educators to deepen their own identity.